Subsurface chemical discharge in Lithuanian area - Diliūnas, Jonas; Karvelienė, Danutė; Jurevičius, Arūnas (Journal of Environmental Engineering and Landscape Management, 2010)
An assessment of groundwater chemical leakage under the Lithuanian hydrogeological conditions, using the classic method of hydrogeological/ hydrograph division and linking it with the chemical leakage. Subsurface chemical discharge is the amount of salts flown by the rivers due to their draining impact on the subsurface. The chemical runoff is determined by two key factors: groundwater runoff yield and total content of dissolved solids (TDS). The value of the groundwater runoff module (the yield from 1 km2) in the river basins of Lithuania ranges from 0.4 to 5.0 l/s km2. TDS values in shallow groundwater drained by the rivers range from 180 to 800 mg/l. The modules of subsurface chemical runoff in the area of Lithuania range from 3–9 to 54 t/year from 1 km2 with the highest values observed in the Baltija uplands and Dainava Plain. During the last decade, the chemical runoff has stabilised due to decline in technogenic load. If compared to the dissolved solids drained by the rivers the subsurface chemical discharge can make up 7–45%. The chemical runoff out for all area of Lithuania, as assessed by the hydrological/hydrogeological technique according to the minimum long‐term runoff and TDS content in the river water of that period, reaches 2.2 mln. t/year of mineral material, about 90% of which come from the Nemunas River basin. To restrict the influence of technogenic pollution on the results of the assessment of underground chemical runoff, only observations done upstream the pollution sources (mainly urban) have been used. The qualitative assessment of the changes in groundwater chemical discharge and flow fluctuations due to technogenic impact has been carried out by applying graphical analysis of the underground chemical runoff module. Article in English. Požeminis cheminis nuotėkis Lietuvos teritorijoje Santrauka. Darbo tikslas – ivertinti požeminį cheminį nuotekį Lietuvos hidrogeologinėmis salygomis, taikant klasikinę hidrologohidrogeologinę hidrografo skaidymo metodiką. Požeminis cheminis nuotėkis – tai druskų kiekis, nutekantis upėmis dėl drenažinio poveikio. Cheminį nuotekį lemia du pagrindiniai veiksniai – požeminio nuotėkio debitas ir vandens bendroji mineralizacija. Požeminio nuotekio modulio dydis (debitas iš 1 km2) Lietuvos teritorijos upių baseinuose kinta nuo 0,4 iki 5,0 l/s km2. Į upes požemiu nutekančio gruntinio vandens bendroji mineralizacija – nuo 180 iki 800 mg/l. Požeminio cheminio nuotekio Lietuvos teritorijoje moduliai yra nuo 3–9 iki 54 t/metus iš 1 km2. Didžiausias požeminis cheminis nuotėkis Baltijos aukštumose bei Dainavos lygumoje. Pastarajį dešimtmetį cheminis nuotėkis stabilizavosi dėl sumažejusios technogeninės apkrovos. Palyginti su bendru mineralinių medžiagų kiekių, nutekančių upėmis, požeminis cheminis nuotėkis gali sudaryti 7–45 %. Visas požeminis cheminis nuotekis Lietuvos teritorijoje, įvertintas pagal minimalų daugiametį nuotekį ir to periodo upių vandens mineralizaciją, siekia 2,2 mln. t/metus mineralinių medžiagų, kurių apie 90 % išplukdoma iš Nemuno baseino. Technogeninio užterštumo įtakai požeminio cheminio nuotėkio vertinimo rezultatams riboti naudoti tik stebėjimu duomenys aukščiau taršos šaltiniu (daugiausia miestų). Požeminio vandens cheminio nuotėkio, kurį lemia technogeninis poveikis, pokyčių kokybinis įvertinimas atliktas nuotėkio modulių grafoanalizės pagrindu. Reikšminiai žodžiai: požeminio nuotėkio modulis, bendroji mineralizacija, požeminio cheminio nuotėkio modulis, gamtinės sąlygos. Подземный химический сток на территории Литвы Резюме. Целью работы было оценить подземный химический сток с использованием расчленения гидрографа рек и выноса химического материала в гидрогеологических условиях Литвы. Подземный химический сток – это количество солей, протекающих в речных водах из-за их дренажного воздействия. Химический сток зависит от двух основных факторов: дебита подземного стока и общей минерализации воды. Модуль подземного стока (дебит с 1 км2 ) речных бассейнов в пределах Литвы меняется от 0,4 до 5,0 л/с с 1 км2 . Общая минерализация грунтовых вод, притекающих в реки, составляет 180–800 мг/л. Модули подземного химического стока в пределах территории Литвы имеют значения от 3–9 до 54 т/год с 1 км2 . Наибольший подземный химический сток наблюдается на терригории Балтийских высот и Дайнавской равнины. В последнее десятилетие химический сток стал более стабильным из-за уменьшающейся техногенной нагрузки. По сравнению с общим стоком минеральных веществ в реках подземный химический сток может составляет 7–45 %. Весь подземный химический сток, оцененный по минимальному многолетнему стоку и минерализации речной воды, составляет 2,2 млн. т/год минерального вещества, из которого 90 % поступает из бассейна р. Нямунас. Для уменьшения техногенного воздействия на результаты расчетов использованы данные химического состава воды только с постов наблюдения, расположенных выше источников загрязнения. Оценка изменения подземного химического стока выполнена графоаналитически с использованием изменения его модуля во времени. Ключевые слова: модуль подземного стока, общая минерализация, модуль химического стока, природные условия. First Publish Online: 10 Feb 2011